ChemInform Abstract: A Rh‐Catalyzed Regio‐ and Stereoselective Route to Enamides: Benzamides as Assembling Reagents. Issue 46 (18th November 2014) - Lee, Dong Jin; Shin, Jinhwan; Yoo, Eun Jeong
Abstract A novel method is elaborated for the preparation of substituted enaminones (III) and (VI) by a Rh‐catalyzed reaction of triazoles (I) and (V) with amides (II).